2009
DOI: 10.1243/13506501jet644
|View full text |Cite
|
Sign up to set email alerts
|

Film-forming properties and traction of non- functionalized polyalkylmethacrylate solutions under transition from elastohydrodynamic lubrication to thin-film lubrication

Abstract: Oil film thickness of the oils containing non-functionalized polyalkylmethacrylate (PAMA) was determined under pure rolling condition between 0.001 and 1 m/s and a temperature of 40 • C with a glass disc-on-steel roller tester. The measurements for PAMA solutions with shortchain alkyl group (C1mix) showed a pronounced enhancement of film thickness in the low speeds, while those for long chain (C16mix) fell on the theoretical line. Adsorption test indicated that the increase in film thickness for C1mix was due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…One of the authors pointed out in the previous report [14] that oil film thickness of polymer solutions at low speeds depended on the type of polymer and combination of polymer and base oil. This is probably because of changes in the rheological properties of polymer solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the authors pointed out in the previous report [14] that oil film thickness of polymer solutions at low speeds depended on the type of polymer and combination of polymer and base oil. This is probably because of changes in the rheological properties of polymer solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The actual film thickness was corrected from the optical one using the RI at high pressure. The RI at atmospheric pressure was measured using an Abbe refractometer at 40 • C, and then RI at high pressure was estimated from the Lorentz-Lorenz formula [14]. The AISI 52100 steel roller was 25.4 mm in diameter in the rolling direction and its surface roughness was Ra of 4 nm.…”
Section: Measurements Of Oil Film Thicknessmentioning
confidence: 99%
“…Interestingly, the existence of the ordered film has been also concluded from the critical point of dynamic film [4,5,22]. Other kinds of lubricants have been utilized to explain the film thickness response to the speed in the TFL regime, such as octamethylcyclotetrasiloxane (OMCTS) [31] and polymers (f-PAMA and OCP) [81], by different researchers. The deviation from linearity of the EHL prediction at low speed has been observed in double logarithmic coordinates in most cases.…”
Section: Effect Of Rolling Speed On Tflmentioning
confidence: 99%
“…The thickening of the film thickness at low speed have been then observed by several different groups. Muraki and Nakamura [58] reported the transition from elastohydrodynamic lubrication to thin film lubrication by using nonfunctionalized polyalkylmethacrylate solutions, as shown in Figure 8. Xiao et al [59] found different film forming performance under high contact pressure up to 3 GPa by using different base oil, indicating that the fluidity and molecular structure significantly affect film formation in TFL regime.…”
Section: Advances In Researchesmentioning
confidence: 99%
“…Film-forming properties of polymers (f-PAMA and OCP) in different base oil reported by Muraki and Nakamura[58].…”
mentioning
confidence: 93%